Peran Iklan dan Kelompok Referensi terhadap Minat Pembelian Ulang Obat Herbal - Dewanti, Retno; Sylvie, Sylvie (Bina Nusantara University, 2010)
In 2010 sales forcast proposed the Herbal product on the world has been target US 80 Billion. The Herbal product was accepted on range in the developed countries and the Forward Countries. Suggest of World Health Organization is until 65% people on the forward countries and 80% people the developed Countries used Herbal Product. The prospect of herbal product is relating with Customer interest towards Herbal product, caused that want to know the essential of determinant variable on the customer interest to repeat buying the Herbal product. The aim research was measure the direct and indirect influences of the advertising role and the group of reference towards the customer interest to repeat buying the herbal product.The methodology used Causal analysis with path analysis. The research respondent is Buyer Herbal Product Ling Shen yao in Jakarta which amount sample is 100 person.The result of research explain the theories although referring Causility among variables which is Advertising of Magazine, the group of reference, Quality perception and customer interest to repeat buying, but the fact of research justified is causality advertising have indirect influence toward customer interest to repeat buying through Quality perception and the other hand the group of reference have direct and indirect influence towards customer interest to repeat buying the herbal product.Â